Underlying Causes of Short Stature in Children Aged 4 to 16 Years Presenting at the Endocrine Clinic of a Tertiary Care Hospital in Pakistan: Underlying Causes of Short Stature in Pakistani Children - Naz, Fizzah; Khan, Wasif Ahmed; Arif, Muzna; Usman, Annayah; Qazi, Muhammad Farrukh; Nisar, Imran; Humayun, Khadija Nuzhat (Pakistan Journal of Health Sciences, 2025)
Short stature is a frequent pediatric presentation that may arise from normal growth variants or underlying pathological conditions. In Pakistan, its burden is heightened by malnutrition, infections, and delayed healthcare-seeking behaviors. Identifying the underlying causes is crucial for timely intervention and better outcomes. Objectives: To determine the underlying causes of short stature in children aged 4–16 years presenting at the Endocrine Clinic of a Tertiary Care Hospital in Pakistan. Methods: This descriptive cross-sectional study was conducted at the Pediatric Endocrinology Clinic, Aga Khan University Hospital, Karachi, from March 2023 to March 2024. All children aged 4–16 years with short stature, defined as height <-2 SD for age and sex or below the 3rd centile, were enrolled. Participants were evaluated for normal variants (familial short stature and constitutional delay of growth and puberty) and pathological causes (endocrine and non-endocrine). Results: Among 384 children, 128 (33.3%) had normal variants, most commonly familial short stature (70.3%). Pathological short stature was found in 256 (66.7%) children, with endocrine disorders predominating (60.9%), mainly growth hormone deficiency, hypothyroidism, panhypopituitarism, and hypogonadism. Non-endocrine causes included rickets, celiac disease, and genetic syndromes. No significant gender differences were observed in the distribution of short stature types. Conclusions: Pathological conditions were the leading cause of short stature, accounting for two-thirds of cases, with endocrine disorders being the most frequent contributors. These findings underscore the importance of timely endocrine evaluation in children presenting with growth concerns.